Native State Single-Cell Printing System and Analysis for Matrix Effects - Li, Qi; Tang, Fei; Huo, Xinming; Huang, Xi; Zhang, Yan; Wang, Xiaohao; Zhang, Xinrong (Analytical chemistry (Washington), 2019)
Mass spectrometry is subject to matrix effects, which causes severe limitations on the analysis of live single cells in their native state. Here, we propose a three-phase droplet-based single-cell printing analysis system (TP-SCP), which can package, extract, separate, print, and analyze live single cells in saline matrixes (such as phosphate buffered saline) with matrix-assisted laser desorption/ionization mass spectrometry. This method can eliminate matrix effects to obtain information on a single cell in their native state. We report that a cell packaging percentage of 44% and single-cell packaging percentage of 88% can be achieved by TP-SCP. The system was capable of processing three to four single cells per second, which was 30 to 40 times higher than the traditional droplet-based microextraction (about 10 s/cell). Additionally, the MCF-7, A2780, 293, and 4T1 cells were screened in our system. The effect of cell viability and heterogeneity analysis was investigated, suggesting that the concentration of monounsaturated phosphatidylinositol and phosphatidylethanolamine both increase in cancer cells. Compared with conventional mass spectrometry, TP-SCP can ensure the accuracy of heterogeneity analysis of live single cells in their native state. Both a principal component analysis and a linear discriminant analysis were used to perform classification and identification of cells with an accuracy of 100%. This method provides an innovative framework for research on cell quality control, cell biology, cancer diagnosis, and prevention.